Ruthenium‐Grafted Vinylhelicenes: Chiroptical Properties and Redox Switching. Issue 47 (6th October 2015) - Srebro, Monika; Anger, Emmanuel; Moore II, Barry; Vanthuyne, Nicolas; Roussel, Christian; Réau, Régis; Autschbach, Jochen; Crassous, Jeanne
Abstract: The properties of mono‐ and bis‐Ru–vinyl[6]helicene complexes (2 a and2 b, respectively), recently synthesized by using molecular engineering of helicenes based on the grafting of lateral organometallic substituents on the π‐helical backbone through a vinyl bridge, are presented. These helicene derivatives are thoroughly characterized, with special attention given to their chiroptical properties and redox switching activity. The UV/Vis and electronic circular dichroism (ECD) spectra of P and M enantiopure species, both in the neutral and oxidized states ([2 a ] . +, [2 b ] . +, and [2 b ] 2+ ), are analyzed with the aid of quantum‐chemical calculations. The extended π‐conjugation facilitated by the vinyl moiety, clearly visible in the electronic structures of2 a, b, introduces new active bands in the ECD spectra that consequently lead to a significant increase in optical rotation of Ru–vinylhelicenes compared with the organic precursors. The vibrational circular dichroism (VCD) spectra were measured and calculated for both the organic and organometallic species and constitute the first examples of VCD for metal‐based helicene derivatives. Finally, the redox‐triggered chiroptical switching activity of2 a, b is examined in detail by using ECD spectroscopy. The modifications of the ECD spectra in the UV/Vis and NIR region are well reproduced and rationalized by calculations. Abstract : Let's switch : Introducing a metal–vinyl moiety onto a helicene core is shown to be a promising, straightforward approach to enhancing the chiroptical properties and conferring multifunctionality on the helicene by endowing redox activity. Example Ru–vinylhelicenes are characterized in detail. The extended π‐conjugation between the Ru center(s) and the helicene through the vinyl bridge determines the unique redox chiroptical switching of these systems.